Examining the Acceptance of Automated Piggery Cleaner System Using UTAUT Model for Hog Business in the Philippines - Bacalso, Fritz; Rendon, Irvin Paul; Campita, Rose Ann; Mobo, Froilan D.; Cutillas, Anesito (Future Science / FSH-PH Publications, 2023)
This study examines the acceptance of automated piggery cleaner systems in the hog business in the Philippines using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. It investigates piggery owners’ perceptions and attitudes toward adopting this technology and its potential impact on cleaning practices, hygiene standards, and productivity. A survey questionnaire was administered to 50 piggery owners in Cebu, Philippines, employing a mixed-methods approach. The analysis reveals that piggery owners generally hold positive perceptions and attitudes towards automated piggery cleaner systems, recognizing their potential benefits in enhancing productivity, efficiency, and career advantages. Factors influencing acceptance, such as performance expectancy, effort expectancy, facilitating conditions, and social influence, were explored. Although the correlation analysis does not show significant relationships between UTAUT constructs and behavioral intention, it emphasizes considering other factors like subjective norms and perceived behavioral control. The findings have important implications for the hog business in the Philippines. Embracing automated piggery cleaner systems can improve cleaning practices, enhance hygiene standards, prevent disease outbreaks, and increase productivity. Collaborative efforts among piggery owners, industry associations, and technology providers are recommended to address concerns and barriers, including providing training and support, ensuring compatibility, and emphasizing voluntary adoption. This study offers valuable insights for pig farmers, industry stakeholders, and policymakers, enabling the adoption of innovative technologies and achieving sustainable and efficient pig farming practices in the Philippines.